A Multi-Scale Approach to Investigate Adhesion Properties of Pseudomonas aeruginosa PAO1 to Geotrichum candidum LG-8, a Potential Probiotic Yeast - Ling Meng; Siduo Zhou; Xiao Xu; Dian Li; Yanfei Lin; Fangxin Lyu; Mingsheng Dong (Foods, 2020)
This study investigated properties of Pseudomonas aeruginosa PAO1 adhesion to Geotrichum candidum LG-8 cells in variable pH and salt conditions. The primary mechanism was revealed by multi-scale microscopy technics. The adhesion of PAO1 to the living fungus occurred within 1 h and was limited at concentrations of bile salts higher than 0.5%. The adhesion efficiency gradually increased to 58.1% with the pH increasing from 2.0 to 7.0 and then decreased to 48.2% at pH 9.0. However, the dead LG-8 has an advantage over the living ones to adhere PAO1 in same pH and bile salt conditions. Optical microscopy showed that both unsterilized and sterilized G. candidum LG-8 cells removed approximately one hundred fold bacteria in 4 h. Laser scanning confocal microscopy (LSCM) analysis indicated that polysaccharides of the fungus contributed to adhesion. Scanning electron microscopy (SEM) analysis proved that syrup-like EPS (extracellular polymeric substances) of LG-8 coating PAO1 was in part a mechanism. Atomic force microscopy (AFM) showed roughness of the LG-8 surface changed in the adhesion process. Furthermore, a pedestal-like structure of bacteria was observed by transmission electron microscopy (TEM) analysis, indicating that the bacteria were also actively involved in the adhesion process. G. candidum LG-8 is a potential candidate for the control of P. aeruginosa PAO1 in the food industry and immunodeficiency patients.